Open Innovation Strategies and Organization Performance of the Telecommunication Industry in Kenya - Muchungu, Anna; Mutua, Justice (European Journal of Business and Strategic Management, 2024)
Purpose: The purpose of this study was to evaluate the relationship between open innovation strategies and organization performance of the telecommunication industry in Kenya. The study was guided by the following objectives: to examine the effect of innovations and innovation strategies on organizational performance; to establish the effect of open innovation strategies on organization performance; to assess the role of organization factors in moderating open innovation strategies; and to identify the open innovation strategies adopted in the telecommunication industry in Kenya. Methodology: The study relied on desktop research to address the existing gaps in the literature. Information for the research was obtained from published literature and information in the public domain. The information was critically reviewed, analyzed, synthesized, and conclusions were drawn. Findings: The findings of this study revealed that collaboration between firms in the telecommunication industry and various stakeholders through open innovation strategies influences the performance of the organizations in the industry. These findings suggest that organizations in the telecommunication industry in Kenya, which adopt open innovation strategies, can effectively innovate and compete in the industry, despite the dominant position of one organization. Unique Contribution to Theory, Practice and Policy: Utilizing the Open Innovation (OI) Theory and the Resource-Based View (RBV) Theory, the researcher explored the relationship between open innovation strategies and organization performance of the telecommunication industry in Kenya. The study deepened our understanding of RBV theory in explaining the dominance of one firm in the telecommunication industry. In addition, the study focused on how organizations are able to access talent and resources using the OI theory framework and therefore are able to innovate and compete. The various stakeholders including customers, suppliers and the Government of Kenya will benefit from this study by having additional insights into open innovation strategies and practices. A key recommendation is to the Communications Authority of Kenya, the regulatory body in the telecommunication industry in Kenya. The regulator should provide an enabling environment which facilitate innovations and collaboration using open innovation framework, benefitting all organizations and stakeholders in the industry.